2015
DOI: 10.1111/nmo.12525
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal mast cell degranulation and gastrointestinal recovery in patients undergoing colorectal surgery

Abstract: Colorectal surgery causes protease release from peritoneal MCs. Protease release does not differ between both types of colectomy (laparoscopy vs laparotomy). However, MC activation is increased in colectomy patients developing POI. Therefore, degranulation of peritoneal MCs as a factor contributing to human POI after colectomy might be considered in future studies as a target to avoid POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
0
17
1
Order By: Relevance
“…in mice, demonstrating a lack of mast cell involvement in the postsurgical delay of intestinal transit . By contrast, a recent study by our group has demonstrated that human POI is associated with mast cell protease release during abdominal surgery, and that the magnitude of this release depends on the severity of intestinal handling . In addition to proteases, several other mast cell products have been shown to modulate the enteric nervous system (ENS) and the intestinal motor patterns, and are therefore likely to be relevant to the development of POI .…”
Section: Discussionmentioning
confidence: 88%
“…in mice, demonstrating a lack of mast cell involvement in the postsurgical delay of intestinal transit . By contrast, a recent study by our group has demonstrated that human POI is associated with mast cell protease release during abdominal surgery, and that the magnitude of this release depends on the severity of intestinal handling . In addition to proteases, several other mast cell products have been shown to modulate the enteric nervous system (ENS) and the intestinal motor patterns, and are therefore likely to be relevant to the development of POI .…”
Section: Discussionmentioning
confidence: 88%
“…These data warrant caution in interpretation of experimental rodent models of mast cell deficiency and pharmacological mast cell inhibitors that may display off‐target effects on non‐mast cell populations that were not recognized earlier . Nevertheless, the currently reported association of mast cell degranulation and POI by Berdun et al ., along with other human studies corroborating degranulation of mast cells in POI‐related surgery, may point toward a non‐redundant role for mast cells in POI, at least in human. One issue that needs attention in this context is the species’ variation in the density of mast cells in the gut of experimental models and clinical settings of POI, ranging from quite scarce (mouse; importantly varying between different strains) to quite abundant (human).…”
Section: Mast Cell Activation By Bowel Manipulationmentioning
confidence: 84%
“…Mast cell degranulation may also be of importance in gut barrier integrity and may play a role in development of sepsis . In the study by Berdun et al ., it is shown that peritoneal mast cell degranulation is associated with GI recovery in the clinical setting . Interestingly, the type of procedure, in this case colectomy vs cholecystectomy, was a more determining factor in the extent of mast cell activation than the surgical approach (open or minimally invasive).…”
Section: Introductionmentioning
confidence: 98%
“…Although MCs can modulate vagal afferents, mediators released during MC degranulation, such as serotonin and histamine, can also act on splanchnic afferents, particularly in inflammatory conditions . We previously demonstrated that intestinal manipulation activates PMCs, but not mucosal MCs (data not shown), in patients undergoing intestinal surgery and in an experimental rat model of POI . It is interesting that we did not observe differences in number or distribution of CTMC within the intestinal wall.…”
Section: Discussionmentioning
confidence: 53%